2017
DOI: 10.1002/fut.21845
|View full text |Cite
|
Sign up to set email alerts
|

The CDS‐Bond Basis Arbitrage and the Cross Section of Corporate Bond Returns

Abstract: We provide a comprehensive empirical analysis on the implication of CDS‐Bond basis arbitrage for the pricing of corporate bonds. Basis arbitrageurs introduce new risks such as funding liquidity and counterparty risk into the corporate bond market, which was dominated by passive investors before the existence of credit default swap (CDS). We show that a basis factor, constructed as the return differential between LOW and HIGH quintile basis portfolios, is a superior empirical proxy that captures the new risks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Our second argument is that arbitrage risk factors, which previously influenced bond prices through an arbitrage channel (Kim, Li and Zhang 2017), are no longer relevant during the post-crisis period. The results of regression (9) used to formally test Assumption 2 are summarized in Table 12.…”
Section: Impact Of Basis Arbitrage Activity On Bond Returnsmentioning
confidence: 97%
See 3 more Smart Citations
“…Our second argument is that arbitrage risk factors, which previously influenced bond prices through an arbitrage channel (Kim, Li and Zhang 2017), are no longer relevant during the post-crisis period. The results of regression (9) used to formally test Assumption 2 are summarized in Table 12.…”
Section: Impact Of Basis Arbitrage Activity On Bond Returnsmentioning
confidence: 97%
“…Despite the puzzling fact that basis negativity persists long after the end of the financial crisis, very few studies focus on the post-crisis period. Kim, Li and Zhang (2017) do not study the basis determinants, but rather analyze the CDS-bond basis from a different angle, exploring the implications of arbitrage trades on corporate bonds' future returns. Using a regression model of the basis on the risk factors inherent to arbitrage activity, they split the basis into two parts.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship of CDS premium vs. corporate bond yield spread (risky bond yield minus riskless bond yield) of the same tenor has been the subject of many empirical studies, for example, Blanco, et al (2005) and Zhu (2006) confirmed a long-run parity relationship between the two credit risk measures. Kim, et al (2017) further investigated the basis (CDS premium vs. corporate bond yield spread) behavior to see whether basis arbitrage is possible. This line of studies again sheds light on whether a theory holds or arbitrage opportunity exists, but offers no practical answer to predicting CDS for corporates without traded bonds of comparable terms.…”
Section: Introductionmentioning
confidence: 99%